2010
DOI: 10.1128/iai.01448-09
|View full text |Cite
|
Sign up to set email alerts
|

Tetratricopeptide Repeat Protein-Associated Proteins Contribute to the Virulence ofPorphyromonas gingivalis

Abstract: Porphyromonas gingivalis is one of the most etiologically important microorganisms in periodontal disease. We found in a previous study that PG1385 (TprA) protein, a tetratricopeptide repeat (TPR) protein, was upregulated in P. gingivalis wild-type cells placed in a mouse subcutaneous chamber and that a tprA mutant was clearly less virulent in the mouse subcutaneous abscess model (M. Yoshimura et al., Oral Microbiol. Immunol. 23:413-418, 2008). In the present study, we investigated the gene expression profile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 55 publications
0
51
0
1
Order By: Relevance
“…; Kondo et al. ) although the mechanism remains to be clarified. Our study also revealed an enrichment of HGP44 (an adhesive domain of gingipains) in vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…; Kondo et al. ) although the mechanism remains to be clarified. Our study also revealed an enrichment of HGP44 (an adhesive domain of gingipains) in vesicles.…”
Section: Discussionmentioning
confidence: 99%
“…Although several P. gingivalis proteins bearing a conservative C-terminal domain (54,78) are apparently secreted by the PorT/Sov-dependent pathway (38), only the surface exposure of RgpA and Kgp was shown to be essential for HK and FXII binding by P. gingivalis. Interestingly, deficiency of a single gingipain, either RgpA or Kgp, exerted only a modest effect, suggesting that neither gingipain alone is absolutely essential for binding of the contact system proteins but that together, RgpA, RgpB, and Kgp seem to cooperate for maximal sorption of the contact system components (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Gliding involves the rapid movement of the semiredundant motility adhesins SprB and RemA along the cell surface (Shrivastava et al, 2013). T9SS-secreted proteins exhibit C-terminal domains (CTDs) considered essential for attachment to the bacterial cell surface by an A-LPS anchor containing anionic polysaccharide repeating units (Kondo et al, 2010; Shoji et al, 2011; Slakeski et al, 2011; Shrivastava et al, 2013). CTD region function as a recognition signal for the T9SS and glycosylation occurs after removal of the CTD region (Shoji et al, 2011; Glew et al, 2012).…”
Section: Secreted Proteins Involved In Surface Colonization In Didermmentioning
confidence: 99%